mult = \x -> \y -> x*y
I am trying to reduce
(mult (1+2)) (2+3)
with each of the strategies:
For both applicative and by-value I get the same (because no intermediate lambda expression contains anything reducible, hence applicative does not do reduction under lambda either)
(mult (1+2)) (2+3) (mult 3) (2+3) (\y -> 3*y) (2+3) (\y -> 3*y) 5 3*5 15
With normal and by-name: I am supposed to substitute
(2+3) into the body of
(mult (1+2)). But that does not have a body, unless I do a reduction. But then it is not normal-order, nor call-by-name, since it is not the outermost I reduce. Hence it seems to me that these evaluation strategies "get stuck". But I am probably misunderstanding smth.
Please show me the correct evaluation.